Monodisperse core-shell poly(methyl methacrylate) latex colloids - Dullens, R; Claesson, M; Derks, D; van Blaaderen, A; Kegel, W (2003)
Monodisperse cross-linked composite PMMA latex particles have been developed. The chemical cross-linking of the PMMA facilitates the preparation of particles consisting of a fluorescent core and a large nonfluorescent shell. These core-shell spheres can be dispersed in a density and refractive index matching mixture. This results in an ideal colloidal hard sphere model system that can be used to study many fundamental problems such as freezing, melting, and the glass transistion using quantitative confocal scanning laser microscopy. Furthermore, precize control over the size and the properties of the core and the shell(s) facilitates other applications of this model system.